2011
DOI: 10.1027/0269-8803/a000042
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Attention in Auditory Sensory Gating Paradigms in Schizophrenia

Abstract: The paired-click paradigm (PCP) is widely used to study sensory habituation or gating in a number of psychiatric and neurological conditions. The classic paradigm does not control for attentional factors. In order to assess the influences of incorporating attentional control measures we administered the auditory PCP (S1–S2) in three different attention (passive, auditory attention to S2, visual attention to a concurrent continuous performance task [CPT]) conditions to a group of chronic, medicated schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Gjini et al (2011 found attention to S2 increased the S1 response in both healthy controls and patients with schizophrenia, while only S2 amplitudes increased as a function of attention in healthy participants. This resulted in improved sensory gating ratios in patients, and a reduced group difference (Gjini et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gjini et al (2011 found attention to S2 increased the S1 response in both healthy controls and patients with schizophrenia, while only S2 amplitudes increased as a function of attention in healthy participants. This resulted in improved sensory gating ratios in patients, and a reduced group difference (Gjini et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al, 2009) and passive tasks (e.g. Patrick et al, 1999;Rentzsch et al, 2007). Gjini et al (2011 found attention to S2 increased the S1 response in both healthy controls and patients with schizophrenia, while only S2 amplitudes increased as a function of attention in healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…An EEG technologist monitored the ongoing EEG to make sure subjects did not drift into drowsiness or sleep. Prior studies showed that only focused attention on the pairs of stimuli (e.g., counting odd pairs embedded among standard pairs) can influence the P50 response or its gating (Guterman et al, 1992; Jerger et al, 1992; Gjini et al, 2011). AERs were recorded from subdural strip and grid electrodes (sampling rate 1000 Hz per channel), with reference to both mastoids (the most common reference used for gating studies).…”
Section: Methodsmentioning
confidence: 99%
“…An additional research question concerns the effects of attention on sensory adaptation. Recent studies have attempted to examine this interaction and, although the findings are still equivocal, there is some evidence for attention‐modulated auditory adaptation (Rosburg et al ., ; Gjini et al ., ). This is of particular interest for both the characterization of adaptation in the general population, and in clinical groups, particularly those with documented attention deficits (i.e.…”
Section: Discussionmentioning
confidence: 97%